THE “TURGENEV GIRL” IN THE CONTEXT OF THE DIALOGUE BETWEEN RUSSIAN AND EUROPEAN CULTURES - Murotova Shakhlo Odiljon qizi (PEDAGOGS, 2025)
Abstract: The “Turgenev girl” is a symbolic figure that emerged in Russian literature during the Golden Age—the 19th century—embodying not only national literary characteristics but also reflecting the broader spiritual and social developments in European culture. This character, found in the works of Ivan Sergeyevich Turgenev, is distinguished by her unique inner world, independent worldview, and the ability to stand against social stereotypes. She is an intellectual and morally steadfast young woman. For more than a century, the “Turgenev girl” has served as a symbolic link between Russian society and European civilization, simultaneously bridging their differences and highlighting their similarities.